Valuation Under Uncertainty - Chen, Houng-Yhi (Journal of Financial and Quantitative Analysis, 1967)
Broadly speaking there are two models to the problem of asset valuation under uncertainty and aversion to risk. Under one, the certaintyequivalent method, each future return is converted to its certainty equivalent and discounted at the pure rate of interest. Under the other, the risk-adjusted discount rate method, each future return is discounted at an appropriate discount rate. The interrelation and validity of these models of asset valuation have come under discussion in two important works on stock valuation.